Custodial symmetry and extensions of the standard model - Montero, J. C.; Pleitez, V. (American Physical Soc, 2006)
We show that the extension of the approximate custodial SU(2)(L+R) global symmetry to all the Yukawa interactions of the standard model Lagrangian implies the introduction of sterile right-handed neutrinos and the seesaw mechanism in this sector. In this framework, the observed quark and lepton masses may be interpreted as an effect of physics beyond the standard model. The mechanism used for breaking this symmetry in the Yukawa sector could be different from the one at work in the vector boson sector. We give three model independent examples of these mechanisms.